Laboratory Evolution of a Saccharomyces cerevisiae × S. eubayanus Hybrid Under Simulated Lager-Brewing Conditions - Gorter de Vries, Arthur R.; Voskamp, Maaike A.; van Aalst, Aafke C. A.; Kristensen, Line H.; Jansen, Liset; van den Broek, Marcel; Salazar, Alex N.; Brouwers, Nick; Abeel, Thomas; Pronk, Jack T.; Daran, Jean-Marc G. (Frontiers in Genetics, 2019)
Saccharomyces pastorianus lager-brewing yeasts are domesticated hybrids of S. cerevisiae x S. eubayanus that display extensive inter-strain chromosome copy number variation and chromosomal recombinations. It is unclear to what extent such genome rearrangements are intrinsic to the domestication of hybrid brewing yeasts and whether they contribute to their industrial performance. Here, an allodiploid laboratory hybrid of S. cerevisiae and S. eubayanus was evolved for up to 418 generations on wort under simulated lager-brewing conditions in six independent sequential batch bioreactors. Characterization of 55 single-cell isolates from the evolved cultures showed large phenotypic diversity and whole-genome sequencing revealed a large array of mutations. Frequent loss of heterozygosity involved diverse, strain-specific chromosomal translocations, which differed from those observed in domesticated, aneuploid S. pastorianus brewing strains. In contrast to the extensive aneuploidy of domesticated S. pastorianus strains, the evolved isolates only showed limited (segmental) aneuploidy. Specific mutations could be linked to calcium-dependent flocculation, loss of maltotriose utilization and loss of mitochondrial activity, three industrially relevant traits that also occur in domesticated S. pastorianus strains. This study indicates that fast acquisition of extensive aneuploidy is not required for genetic adaptation of S. cerevisiae x S. eubayanus hybrids to brewing environments. In addition, this work demonstrates that, consistent with the diversity of brewing strains for maltotriose utilization, domestication under brewing conditions can result in loss of this industrially relevant trait. These observations have important implications for the design of strategies to improve industrial performance of novel laboratory-made hybrids.